Proteolytic potential of enzymes produced by candida parapsilosis and rhodotorula. Mucilaginosa isolated from liquid whey - Monte, Aline Marques (2019)
The search for yeast with proteolytic activity that can be explored in technology and product innovation was the objective of this study to isolate and identify strains present in liquid whey and evaluate the proteolytic activity of isolates. From the isolated strains were selected for molecular identification, those with proteolytic activity. Verification of proteolytic activity was performed on milk agar and visualized by a translucent halo. Four strains belonging to two yeast species were identified as protease producers. Whey is promising in microbial sources of biotechnological interest and C. parapsilosis (ES01) and R. mucilaginosa (ES04) strains were good protease producers in commercial agar-like milk agar. These results indicate the proteolytic potentiality of strains isolated from whey.